(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
This article examines how the misunderstanding of the implementation of the Qur’anic text amar ma’ruf nahi munkar by extreme Islamic groups (HTI, Salafi-Wahabi, and FPI), especially in Indonesia. Presenting the phenomenon that often occurs and the response to acts of violence accompanied by the destruction of facilities is a form of implementing verses that are not in line with the nature of Islam, which was revealed as a religion that perfects all things, including morals. This article is written with a qualitative method using library research steps by referring to appropriate, relevant, and accurate references that can later be accounted for. This article aims to find out how mistakes have been made in interpreting the text of amar ma’ruf nahi mungkar by extreme Islamic groups. The findings of this research are that the Qur’anic verse amar ma’ruf nahi munkar fails to be understood by extreme Islamic groups. The verse upholds goodness and prevents evil instead of being applied with violence. The meaning contained in word "ma’ruf" means "with wisdom" in the realization that amar ma’ruf nahi munkar also has a message that Islam is a religion that invites goodness, safety, benefit, and without violence. This research article will add knowledge and additional study material for academics regarding the dynamics of religious movements, especially in Indonesia. Artikel ini mengkaji tentang bagaimana kesalahpahaman implementasi teks al-Qur’an amar ma’ruf nahi munkar oleh kelompok Islam ekstrem (HTI, Salafi-Wahabi, dan FPI) khususnya di Indonesia. Dengan menampilkan fenomena yang kerap kali terjadi dan respon tindakan kekerasan disertai pengerusakan fasilitas merupakan wujud implementasi ayat yang tidak selaras dengan hakikat Islam yang turun sebagai agama penyempurna segala hal, termasuk akhlak. Artikel ini ditulis dengan metode kualitatif dengan menggunakan langkah library research, dengan merujuk pada referensi yang tepat, relevan dan akurat nantinya bisa dipertenggungjawabkan. Tujuan ditulisnya artikel ini yaitu untuk mengetahui bagaimana kesalahan yang selama ini kurang tepat dalam memaknai teks amar ma’ruf nahi mungkar oleh kelompok islam ekstrem. Temuan dari penelitian ini adalah, ayat Qur’an amar ma’ruf nahi munkar gagal dipahami oleh kelompok Islam yang berhaluan ekstrem. Ayat tersebut digunakan untuk menegakkan kebaikan dan mencegah kemungkaran justru diterapkan dengan kekerasan. Padahal makna yang terkandung dalam kata “ma’ruf” berarti “dengan bijaksana”. Pada sadarnya amar ma’ruf nahi munkar juga memiliki pesan bahwa Islam agama yang mengajak kebaikan, keselamatan, kemaslahatan, dan tanpa kekerasan. Artikel penilitian ini nantinya akan menambah pengetahuan dan tambahan bahan kajian para akademisi-agamawan terkait dinamika gerakan keagamaan khususnya di Indonesia.